2022
DOI: 10.1038/s41598-022-07910-0
|View full text |Cite
|
Sign up to set email alerts
|

Field trials reveal the complexities of deploying and evaluating the impacts of yeast-baited ovitraps on Aedes mosquito densities in Trinidad, West Indies

Abstract: The use of lure-and-kill, large-volume ovitraps to control Aedes aegypti and Aedes albopictus populations has shown promise across multiple designs that target gravid females (adulticidal) or larvae post-oviposition (larvicidal). Here we report on a pilot trial to deploy 10 L yeast-baited ovitraps at select sites in Curepe, Trinidad, West Indies during July to December, 2019. Oviposition rates among ovitraps placed in three Treatment sites were compared to a limited number of traps placed in three Control area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However due to conveniences yeast was selected for further evaluation. This is evident in other studies that have shown the effectiveness of yeast baited traps and ovitraps at luring different mosquito species including Aedes [17,18,45]. While yeast was not as attractive as fermented grass, it was far simpler to use as bakers yeast is cheap, standardised and is widely available.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However due to conveniences yeast was selected for further evaluation. This is evident in other studies that have shown the effectiveness of yeast baited traps and ovitraps at luring different mosquito species including Aedes [17,18,45]. While yeast was not as attractive as fermented grass, it was far simpler to use as bakers yeast is cheap, standardised and is widely available.…”
Section: Discussionmentioning
confidence: 88%
“…Lethal ovitraps (gravid traps) such as Gravid Aedes Trap (GAT) and Autocidal Gravid Ovitrap (AGO) are among the most widely used traps for sampling Aedes mosquitoes and primarily designed to capture gravid mosquitoes [15]. These are passive traps that use water and organic materials to attract mosquitoes seeking a place for oviposition [16][17][18]. Mosquitoes are captured by either a sticky surface, oil, or insecticide lined inside the GAT [12] or an adhesive sticky board in AGO traps [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to convenience, yeast was selected for further evaluation. This is evident in other studies that have shown the effectiveness of yeast-baited traps and ovitraps at luring different mosquito species including Aedes [17,18,45]. While yeast was not as attractive as fermented grass, it was far simpler to use as baker's yeast is cheap, standardized, and widely available.…”
Section: Discussionmentioning
confidence: 90%
“…Lethal ovitraps (gravid traps) such as Gravid Aedes Trap (GAT) and Autocidal Gravid Ovitrap (AGO) are among the most widely used traps for sampling Aedes mosquitoes and are primarily designed to capture gravid mosquitoes [ 15 ]. These are passive traps that use water and organic materials to attract mosquitoes seeking a place for oviposition [ 16 , 17 , 18 ]. Mosquitoes are captured by either a sticky surface, oil, or insecticide lined inside the GAT [ 12 ] or an adhesive sticky board in AGO traps [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traps called ovitraps were used for egg collection in the field, which consist of a black plastic material (10.5 cm in diameter and 15 cm in height) with removable pressed wooden paddles filled with 495 mL of tap water, and 1 mL of beer yeast solution (0.04%) was added to increase attractiveness and stimulate egg deposition by females 20 , 35 - 36 .…”
Section: Methodsmentioning
confidence: 99%